Bioelectrical impedance phase angle in sport: a systematic review - Olivia Di Vincenzo; Maurizio Marra; Luca Scalfi (Taylor & Francis Group, 2019)
Background Phase angle (PhA) is a raw BIA variable that has been gaining attention in recent years because it is supposed to be an index of the ratio between extracellular and intracellular water, body cell mass, and cellular integrity. The aim of this systematic review was to evaluate the variability of PhA between different sports and its relationships with sport performance. Additionally, we investigated whether PhA depends on gender or age, and analyzed the differences between athletes and controls. Methods A systematic research using PubMed, Scopus and Web of Science up to June 2019 was performed. Selection criteria included studies on subjects who practice sports in planned and continuous modality at competitive or elite level. Results Thirty-five papers met the inclusion criteria (twenty-one cross-sectional data, fourteen longitudinal data). A few but convincing studies have shown that mean PhA is higher in athletes vs. controls. PhA increases with age and is likely to be higher in male than female athletes. A large variability in PhA is observed for the same sport, while it is still uncertain to what extent PhA differs between various sports. There are no clear relationships of PhA with sport performance or training/untraining. Conclusion It is still to be defined to what extent PhA varies between different sports and changes with training/untraining. It can be argued that for a given sport much more data should be collected in a systematic way and for a period of time appropriate in order to determine changes and trends. This is even more crucial in the case of intervention studies.